Legal responsibilities of electronic media towards social work (Kurdistan Region for example) - ئه‌حمه‌د, پ.ی.د.كارزان محه‌مه‌د ئه‌حمه‌د (Sulaimani Journal for Humanities, 2026)
Due to the development of communication technology, media science has an effective role in providing many services to society, the most obvious of which is to facilitate the exchange of messages and awareness processes of citizens, especially in finding job opportunities. The main topic of this research, the legal responsibilities of electronic media towards social work service in the Kurdistan Region, in a scientific method, tries to discuss the purpose of the research and focuses on the legal duties and roles of electronic media, especially social networks, in the awareness of social workers towards their duties, discipline, rights, and responsibilities. The problem of the research, in addition to determining the legal duties and rights of the media in this field, is how to direct the media to solve the problems facing social work services in the Kurdistan Region. The first part of the study discusses the role of social networks in promoting social work services. It presents the concept of social networks and their characteristics, as well as the role of social networks in creating social work job opportunities. The second part is about the dangers of social networks on social work services. Individual and public rights are evaluated in light of the laws of the Kurdistan Region and Iraq. In the third part, the responsibilities of social networks towards social work are discussed from both professional and legal perspectives. In the practical section, based on grounded theory and through in-depth discussions with experts, we presented an appropriate model to determine the responsibilities of the media, to develop human capacity for social work for now and in the future in the Kurdistan Region. At the end of the study, several recommendations for directing electronic media for the reform and development of social work services are presented.
Keywords: Responsibility of Electronic Media; Social Work; Kurdistan Region